Analisis Kognitif Taktik Pengajaran Bahasa Arab Pada Siswa ADHD - Laili Mas Ulliyah Hasan; Siti Durotun Naseha; Muhammad Rido'i (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2024)
This study aims to analyze the cognitive aspects of Arabic teaching tactics specifically designed for students with Attention Deficit Hyperactivity Disorder (ADHD) in the eighth grade at MTs Wachid Hasyim Surabaya, one of the first inclusive schools in East Java. ADHD can affect the ability to focus and self-control, requiring innovative and adaptive teaching approaches. This study uses qualitative analysis methods to evaluate various teaching tactics implemented in the context of Arabic language education for ADHD students in this inclusive school environment. Data were collected through classroom observations, interviews with educators, and assessments of student progress. The research findings indicate that the use of approaches involving multisensory activities, clear structure, and lessons broken into smaller segments can enhance the engagement and learning outcomes of students with ADHD. These results provide practical guidance for educators at MTs Wachid Hasyim Surabaya in designing more effective and responsive teaching tactics to meet the needs of eighth-grade students with ADHD.